Facile one pot in situ synthesis of ZnS–ZnIn2S4 composite for improved photocatalytic applications. (February 2021) - Janani, R.; Melvin, Ambrose A.; Singh, Shubra
Abstract: Present work utilizes solar-driven photocatalysis as an eco-friendly, green technology to degrade organic contaminants in water. In situ synthesis of ZnS–ZnIn2 S4 composite was carried out with one pot facile hydrothermal route. The as prepared composite was characterized with X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Diffuse Reflectance Spectroscopy (DRS). The composite was found to have an effective optical bandgap of 2.82 eV explicating its activity in the visible region of solar spectrum. Photoactivity of the composite was utilized for degradation of organic contaminants (e.g. Methylene Blue, Ciprofloxacin) in water under UV, visible light and direct sunlight irradiation. The efficiency of the catalyst and kinetics of degradation are discussed in detail. The composite also shows an improved photocurrent density of 1.14 μA/cm 2 and a photocatalytic degradation rate constant of 0.041 min −1 . This work provides an insight to the development of a novel in situ composite with enhanced photocurrent generation and improved photocatalytic activity that can be utilized for environmental remediation applications. Highlights: One step in-situ ZnS-ZnIn2 S4 composite heterostructure formation. ZnS-ZnIn2 S4 composite has red-shifted the activity of ZnS from UV region to visible region of the solar spectrum. Photocatalytic application towards degradation of Methylene Blue and Ciprofloxacin under UV, Visible and direct sunlight.